2007
DOI: 10.1158/0008-5472.can-06-3612
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin SEMA3F Affects Multiple Signaling Pathways in Lung Cancer Cells

Abstract: Loss of SEMA3F occurs frequently in lung cancer and correlates with advanced stage of disease. We previously reported that SEMA3F blocked tumor formation by H157 lung cancer cells in a rat orthotopic model. This was associated with loss of activated A V B 3 integrin, impaired cell adhesion to extracellular matrix components, and down-regulation of phospho-extracellular signal-regulated kinase 1/2 (ERK1/2). These results suggested that SEMA3F might interfere with integrin outside-in signaling. In the present re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 39 publications
5
64
0
Order By: Relevance
“…Our results are in agreement with earlier studies proposing that SEMA3B and SEMA3F act as tumor suppressors (20)(21)(22). Downregulation of SEMA expression in human tumors is attributed to LOH and promoter hypermethylation (46). Consistently, SEMA3B and SEMA3F overexpression in tumor cell lines induced apoptosis, inhibited cell proliferation, and colony formation in soft agar (15,20,22).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with earlier studies proposing that SEMA3B and SEMA3F act as tumor suppressors (20)(21)(22). Downregulation of SEMA expression in human tumors is attributed to LOH and promoter hypermethylation (46). Consistently, SEMA3B and SEMA3F overexpression in tumor cell lines induced apoptosis, inhibited cell proliferation, and colony formation in soft agar (15,20,22).…”
Section: Discussionsupporting
confidence: 93%
“…4935). In addition, we showed that SEMA3F protein correlated negatively with VEGF in lung cancer (Brambilla et al, 2000), and recently demonstrated that SEMA3F reduced VEGF mRNA level and HIF-1a protein level (Potiron et al, 2007). Lastly, intraperitoneal administration of recombinant extracellular SEMA6A in mouse inhibited both bFGF/VEGF and tumour cell line-induced neovascularisation (Dhanabal et al, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…However, SEMA3B, like SEMA3F, is described as a tumour suppressor gene (Tomizawa et al, 2001;Tse et al, 2002). SEMA3F acts as a tumour suppressor gene by reducing angiogenesis and metastasis, probably through the inhibition of integrinmediated adhesion and VEGF expression Kessler et al, 2004;Bielenberg et al, 2004;Kusy et al, 2005;Futamura et al, 2007;Potiron et al, 2007). SEMA3B and SEMA3F are also direct p53 targets (Ochi et al, 2002;Futamura et al, 2007).…”
mentioning
confidence: 99%
“…Consistently, Sema3F can induce endothelial cell collapse [63], repel endothelial cells and inhibit their survival [59], and this anti-angiogenic effect is synergistically enhanced by the addition of Sema3A [34]. At the molecular level, it has been shown that Sema3F inhibits multiple signaling pathways in cancer cells [63,64]; however, whether these pathways are also affected in endothelial cells remains unclear. While it is clear that Sema3F can function as a potent tumor suppressor in vivo, further studies are required to understand the molecular mechanism behind this function and the role that Sema3F expression plays in cancer development and progression.…”
Section: Sema3fmentioning
confidence: 97%